Brain Ultrasonography in Neurocritical Care - Shrestha, Gentle S; Acharya, Pragya; Khanal, Kishor; Robba, Chiara (Journal of Nepalese Society of Critical Care Medicine, 2026)
Ultrasonography (USG) has emerged as a vital bedside tool for diagnosis and for serial evaluation of response to the treatment in critically ill patients. In neurocritical care, brain ultrasonography offers unique advantages including the assessment of increased intracranial pressure (ICP), via midline shift measurement, cerebral blood flow measurement via transcranial doppler (TCD) and nerve sheath diameter (ONSD) monitoring. Recent technological innovations, through the incorporation of artificial intelligence (AI) and machine learning algorithms, have enhanced point-of care ultrasound (POCUS) by improving diagnostic accuracy and reducing operator dependency. The development of portable, handheld ultrasound devices have further increased accessibility, enabling real-time decision making even in resource-limited settings. However, the application of brain ultrasonography in neurocritical care is still limited due to a lack of knowledge and standardized training programs. This review synthesizes current evidence and provides practical guidance on integrating brain ultrasonography into neuro intensive care, addressing a critical need for broader clinical adoption.